Porous carbon and silicon carbon material and preparation method and application thereof
By regulating the pore structure of porous carbon and filling carbon particles, the problem of high expansion rate of silicon carbon negative electrode materials is solved, and high-strength and low-expanded silicon carbon materials are achieved, which improves the performance and safety of the battery.
Patent Information
- Application Number
- CN202411835603.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
AI Technical Summary
The significant volume expansion problem of silicon-carbon anode material during lithium embedding limits its use in the anode and affects the cycle life and safety of the battery.
By regulating the porous structure of porous carbon, including the proportion and shape of mesoporous and micropores, filling spherical or spindle-shaped carbon particles, and using processes such as CO2 activation and silane deposition, silicon carbon materials with high strength and low expansion characteristics are prepared.
It significantly improves the performance of silicon carbon negative electrode, achieves the dual advantages of high strength and low expansion, extends the cycle life of the battery and improves safety, while having advantages in cost, time and safety.
Smart Images

Figure CN119725523A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a porous carbon, silicon-carbon material and a preparation method and application thereof. Background Art
[0002] Silicon-carbon anode materials have attracted widespread attention due to their extremely high theoretical energy density (about 3600mAh / g), especially in terms of low expansion, fast charging and high energy density. When the silicon content is 50%, the gram capacity of silicon-carbon anode materials can reach 1900 mAh / g, and its tap density is higher than that of traditional graphite anode materials, thus increasing the volume energy density to more than 5 times that of graphite anode.
[0003] However, in practical applications, one of the main challenges facing silicon-carbon anode materials is their significant volume expansion during lithium insertion. This expansion not only limits the doping ratio of silicon-carbon materials in the anode, but also may cause damage to the internal structure of the battery, thereby affecting the cycle life and safety of the battery. Specifically, in a 4.50V lithium cobalt oxide system, when the compaction density of the lithium cobalt oxide positive electrode is 4.2g / cm³ and the compaction density of the graphite anode after lithium supplementation is 1.7g / cm³, the thickness ratio of the two is close to 1:1. In contrast, the thickness change of the traditional graphite anode in the fully lithium-intercalated state is about 15%, resulting in a final expansion rate of the entire battery of about 6%. The expansion rate of silicon-carbon anode materials under the same conditions can be as high as 80% or more, which severely limits the use of silicon-carbon materials in the anode, usually not exceeding 10%.
[0004] The significant expansion of silicon-carbon anode materials is mainly attributed to their unique structural characteristics, namely the non-uniform distribution of silicon particles in the porous carbon matrix. The adsorption mechanism of porous carbon and the deposition process of silane compounds work together to form a tree-like network structure. In this structure, the adsorption capacity of porous carbon in different regions varies, resulting in uneven filling density of silicon nanoparticles in the voids of the anode material, further exacerbating the expansion effect of the material.
[0005] Therefore, adjusting the structure of porous carbon has a crucial impact on reducing the expansion rate of silicon-carbon negative electrode materials. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the defect of the prior art that the adsorption degree of porous carbon in different areas is inconsistent, resulting in uneven filling of silicon particles, and to provide a porous carbon, silicon-carbon material and preparation method and application thereof. The present invention significantly improves the performance of the silicon-carbon negative electrode by regulating the pore structure of the porous carbon, achieving the dual advantages of high strength and low expansion. The preparation method of the present invention has obvious advantages in terms of cost, time and safety.
[0007] The present invention solves the above technical problems through the following technical solutions.
[0008] The present invention provides a porous carbon, the pore structure of which includes mesopores and micropores;
[0009] In the pore structure, the pore volume of the mesopores accounts for 3-20%, and the pore volume of the micropores accounts for 80-97%; the adsorption-desorption isotherms of the mesopores are one or more of an H1 hysteresis loop, an H2 hysteresis loop, and an H3 hysteresis loop;
[0010] The pore structure is filled with carbon particles, and the carbon particles are spherical carbon particles or spindle-shaped carbon particles.
[0011] In the present invention, the pore volume of the pore structure can be 0.7-1.3 cm 3 / g.
[0012] In the nitrogen adsorption-desorption isotherm, when the isotherms do not overlap during adsorption and desorption, a mesoporous hysteresis loop will be formed, and IUPAC (International Union of Pure and Applied Chemistry) divides it into five types: H1-H5. In the present invention, preferably, when the adsorption-desorption isotherm of the mesopore is an H1-type hysteresis loop and / or an H2-type hysteresis loop, the ID / IG of the porous carbon is 1.2-0.8, such as 0.99, 0.98 or 0.97; when the adsorption-desorption isotherm of the mesopore is an H3-type hysteresis loop, the ID / IG of the porous carbon is 1.15-0.75, such as 0.97, 0.96 or 0.95; the ID / IG value refers to the intensity ratio of the Raman D peak to the G peak.
[0013] In the present invention, preferably, the adsorption-desorption isotherm of the mesopores is an H3 type hysteresis loop.
[0014] In the present invention, preferably, the spherical carbon particles are attached to the pore walls in a point contact manner.
[0015] In the present invention, preferably, when the carbon particles are spherical carbon particles, the diameter thereof is 15-50 nm, for example, 50 nm.
[0016] In the present invention, preferably, the spindle-shaped carbon particles are attached to the pore walls in line contact or surface contact.
[0017] In the present invention, preferably, when the carbon particles are spindle-shaped carbon particles, the width of the particle size is 4-28 nm and the length is 190-300 nm, for example, the width is 20 nm and the length is 300 nm.
[0018] The present invention also provides a method for preparing porous carbon, the method comprising the following steps: carbonizing and activating a mixture containing a carbon source and a template to prepare porous carbon;
[0019] The template is a spherical template or a shuttle-shaped template. The particle size of the spherical template is 5-200 nm, the length of the shuttle-shaped template is 250-350 nm, the width is 20-40 nm, and the aspect ratio is 9-17.5. The material of the template is one or more of silicon dioxide, starch, cellulose nanocrystals, and polymer materials with a molecular weight of 5000-50000.
[0020] The mass ratio of the template to the carbon source is (5-50):100.
[0021] In the present invention, the particle size of the spherical template agent is 20-80 nm, for example, 50 nm.
[0022] In the present invention, the material of the spherical template agent can be starch.
[0023] In the present invention, the material of the shuttle-shaped template can be cellulose nanocrystals. Cellulose nanocrystals have high crystallinity and are more conducive to analyzing the influence of the pore structure of porous carbon on its mechanical strength and rate performance due to the lack of interference from other functional groups.
[0024] The cellulose nanocrystals can be prepared by a hydrochloric acid method, which generally refers to using hydrochloric acid as a catalyst to decompose cellulose into cellulose nanocrystals through a hydrolysis reaction.
[0025] In the hydrochloric acid method, the molar concentration of the hydrochloric acid aqueous solution may be 3-5 mol / L, for example 4 mol / L.
[0026] In the hydrochloric acid method, the mass ratio of cellulose to hydrochloric acid in the hydrochloric acid aqueous solution may be 10:(40-50), for example, 10:43.8.
[0027] In the hydrochloric acid method, the reaction temperature may be 70-90°C, such as 80°C.
[0028] In the hydrochloric acid method, the reaction time may be 2-4 hours, for example 3 hours.
[0029] In the present invention, the carbon source may be a resin carbon source and / or a biomass carbon source.
[0030] The resin carbon source may be selected from one or more of phenolic resin, epoxy resin, furan resin, polyacrylic resin, polyurethane resin and polyacrylonitrile resin, such as phenolic resin.
[0031] Wherein, preferably, when the carbon source is a resin carbon source, the mixture also includes a curing agent. Adding a curing agent can control the shape of the resin carbon source.
[0032] The curing agent can be selected from one or more of urotropine, ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, hexamethylenetetramine, aniline, p-toluenesulfonic acid, formaldehyde, benzenesulfonyl chloride, p-toluenesulfonyl chloride, ethyl sulfate, petroleum sulfonic acid, dodecylbenzenesulfonic acid, polyoxymethylene, maleic anhydride, phthalic anhydride, isocyanate, pyridine, benzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide and cyclohexanone peroxide, such as urotropine.
[0033] The mass ratio of the resin carbon source to the curing agent is (10-20):1, for example, 16.67:1.
[0034] In the present invention, the mass ratio of the template to the carbon source is preferably 5:1000, 10:1000, 15:1000, 20:1000, 25:1000, 30:1000, 35:1000, 40:1000, 45:1000 or 50:1000. In the present invention, the content of the template is closely related to the strength of the product. If the content of the template is excessive, although the phenomenon of silicon expansion can be alleviated to a certain extent, the strength of the product is reduced.
[0035] In the present invention, a drying step may be included before the carbonization; the drying is preferably spray drying.
[0036] The spray drying temperature may be 100-150°C, for example 130°C.
[0037] In the present invention, before the carbonization, the particle diameter of the precursor may be 5-20 μm, for example, 8 μm.
[0038] In the present invention, the carbonization can be carried out by staged heat treatment; preferably, the first stage heating rate is 1-10℃ / min, heating to 150-250℃, and keeping warm for 0.5-3h; the second stage heating rate is 1-10℃ / min, heating to 400-800℃, and keeping warm for 0.5-12h.
[0039] In a preferred embodiment, the carbonization steps are as follows: first, heat up at a heating rate of 4°C / min for 50 minutes, and keep at 200°C for 1 hour; then, heat up at a heating rate of 4°C / min for 113 minutes, and keep at 652°C for 1 hour.
[0040] In the present invention, the carbonization is carried out under an inert atmosphere, and the gas flow rate of the inert atmosphere is 0.5-3 L·kg -1 min -1 , for example 1 L kg -1 min -1 .
[0041] In the present invention, after the carbonization, the particle size D50 of the material may be 5-20 μm, for example 8.1 μm.
[0042] In the present invention, after the carbonization, when the carbon particles are spherical carbon particles, the diameter thereof is 20-60 nm; when the carbon particles are spindle-shaped carbon particles, the width of the particle diameter is 5-30 nm and the length is 200-300 nm.
[0043] In the present invention, the activation can be carried out by CO 2 Activated or alkaline activated.
[0044] Among them, CO 2 During activation, the gas flow rate is preferably 1-5 L·kg -1 min -1 , for example 2L·kg -1 min -1 The temperature is preferably 450-800°C, such as 550°C; the time is preferably 5-15h, such as 10h. In the present invention, the micropore development can be adjusted during the activation process to affect the pore volume ratio.
[0045] The present invention also provides a porous carbon, which is prepared by the above preparation method.
[0046] The present invention also provides a silicon-carbon material, which is a core-shell structure. The core of the core-shell structure includes the porous carbon and silicon particles, and the shell of the core-shell structure is a carbon coating layer.
[0047] The present invention also provides a method for preparing a silicon-carbon material, wherein the porous carbon is sequentially subjected to silane deposition and carbon coating.
[0048] In the present invention, the gas for silane deposition may be a mixed gas of silane and argon. Preferably, the mixed gas is 20% silane and 80% argon, where % refers to volume percentage;
[0049] In the present invention, the ventilation volume of the silane deposition can be 0.2-1 L·kg -1 min -1 , for example 0.5 L kg -1 ·min -1 ;
[0050] In the present invention, the temperature of the silane deposition may be 500-600°C, for example 550°C;
[0051] In the present invention, the silane deposition time may be 6-10 hours, for example 8 hours.
[0052] In the present invention, preferably, the carbon coating is in the form of acetylene coating.
[0053] The ventilation rate of acetylene is preferably 1-3 L·kg -1 ·min -1 , for example 2 L·kg -1 ·min -1 .
[0054] The ventilation time of acetylene is preferably 500-700 min, for example 600 min.
[0055] Wherein, the temperature of the acetylene coating is preferably 500-700°C, such as 600°C.
[0056] The present invention also provides a silicon-carbon material, which is prepared by the above preparation method.
[0057] The present invention also provides an application of the porous carbon or the silicon-carbon material in a battery.
[0058] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0059] The reagents and raw materials used in the present invention are commercially available.
[0060] The positive and progressive effects of the present invention are:
[0061] The present invention significantly improves the performance of the silicon-carbon negative electrode by regulating the pore structure of porous carbon, achieving the dual advantages of high strength and low expansion. The preparation method of the present invention has obvious advantages in terms of cost, time and safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a schematic diagram of the structure of the porous carbon prepared in Example 5.
[0063] Figure 2 This is a schematic diagram of the structure of the porous carbon prepared in Example 15.
[0064] Figure 3 This is the SEM image of the porous carbon prepared in Example 5.
[0065] Figure 4 The nitrogen adsorption-desorption isotherms of the porous carbons prepared in Example 5 (starch) and Example 15 (cellulose nanocrystals) are shown. DETAILED DESCRIPTION
[0066] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0067] The template agent sources used in the following examples are as follows:
[0068] (1) Spherical starch was purchased from Shansi Technology Co., Ltd., model number SG068, and its particle size was about 50 nm.
[0069] (2) Cellulose nanocrystals are prepared by the hydrochloric acid method, that is, hydrochloric acid is used as a catalyst to decompose cotton cellulose into cellulose nanocrystals through a hydrolysis reaction. Specifically:
[0070] The amount of hydrochloric acid aqueous solution used is 0.3L, the molar concentration of the hydrochloric acid aqueous solution is 4mol / L (the mass of hydrochloric acid is calculated as follows: 0.3L×4 mol / L×36.5=43.8g), and the mass ratio of cotton cellulose to hydrochloric acid in the hydrochloric acid aqueous solution is 10:43.8. The reaction temperature is 80°C and the reaction time is 3h. The reaction is terminated by adding an excess of deionized water, wherein the amount of deionized water added is 3 times the volume of the hydrochloric acid aqueous solution.
[0071] After the reaction is completed, the solution is dialyzed several times with 5 times deionized water until the pH value is 7.5, and then spray-dried by spray drying technology to obtain cellulose nanocrystals with a particle size of about 20-40 nm in width and 250-350 nm in length.
[0072] Examples 1-20
[0073] (1) Preparation of precursor: 1 kg of phenolic resin, 2 kg of alcohol, 60 g of hexamethylenetetramine and spherical starch or cellulose nanocrystals were mixed using a high-speed dispersing homogenizer at a dispersing speed of 2000 r / min for 60 min. The mixture was spray dried at 130 °C to a particle diameter of 8 μm.
[0074] The amount of spherical starch or cellulose nanocrystals used is shown in Table 1 below.
[0075] (2) Preparation of carbon materials: The powder was placed in a cyclotron furnace with a rotation speed of 10 r / min and a nitrogen gas flow rate of 1 L kg -1 min -1 ; First, the temperature was raised at a heating rate of 4°C / min for 50min, and then kept at 200°C for 1h to crosslink the phenolic resin; then, the temperature was raised at a heating rate of 4°C / min for 113min, and then kept at 652°C for 1h. The particle size D50 of the obtained carbon material was 8.1μm.
[0076] (3) Activation of carbon materials: using CO 2 The obtained carbon material is activated, CO 2 Gas flow rate is 2L·kg -1 min -1 , maintain the activation temperature at 550℃ and the time for 10h.
[0077] (4) Silane deposition: The gas was switched to a silane mixture (20% silane and 80% argon by volume), and the deposition was carried out at 550°C for 8 h with a ventilation volume of 0.5 L kg -1 ·min -1 .
[0078] (5) Acetylene coating: The ventilation volume of acetylene is 2L·kg -1 ·min -1 , time is 600min, temperature is 600℃.
[0079] Table 1
[0080]
[0081] Comparative Example 1
[0082] Compared with Example 1, the comparative example did not add a template (spherical starch or cellulose nanocrystals), which is a traditional silicon-carbon negative electrode preparation process.
[0083] Effect Example 1 Microstructure Characterization
[0084] Figure 1 is a schematic diagram of the structure of the porous carbon obtained in Example 5, Figure 3 This is a SEM image of the porous carbon prepared in Example 5. It can be observed from the image that the porous carbon structure includes mesopores and micropores, and the pore structure is filled with spherical carbon particles, which are attached to the pore walls in a point contact manner.
[0085] Figure 2 This is a schematic diagram of the structure of the porous carbon obtained in Example 15. The porous carbon structure includes mesopores and micropores. The pore structure is filled with spindle-shaped carbon particles, and the spindle-shaped carbon particles are attached to the pore walls in line contact or surface contact.
[0086] Effect Example 2 Physical and Chemical Properties
[0087] The following effect tests were performed on the intermediate products and the final silicon-carbon materials of the above embodiments and comparative examples:
[0088] (1) Carbon content test: Use high-frequency carbon-sulfur analyzer (model DK-606).
[0089] Residual carbon rate: obtained based on the carbon mass after carbonization and before activation / precursor mass;
[0090] Carbon yield: obtained based on porous carbon mass / precursor mass;
[0091] Silicon content: obtained using the formula "Silicon content = 1-carbon content-sulfur content".
[0092] (2) Specific surface area: measured using ASAP2020 from Micromeritics;
[0093] (3) ID / IG: Raman spectroscopy test (Raman): There are two characteristic peaks in the Raman spectrum curve of silicon-carbon materials, with the peak values located at 1310~1360cm -1 The peak between is the disorder peak (D peak); located at 1560~1610cm -1 The peak between the D peak and the G peak is the graphite peak (G peak). The integrated area ratio of the D peak to the G peak (ID / IG) can be used to characterize the disorder or graphitization degree of the silicon-carbon material. The smaller the ID / IG, the lower the disorder and the higher the graphitization degree, and the stronger the buffering effect of the obtained material on the expansion of silicon-intercalated lithium.
[0094] (4) Particle size test: The D50 particle size of the silicon-carbon material was tested using a laser particle size analyzer at 0 MPa, 10 MPa, 15 MPa and 20 MPa.
[0095] (5) Tap density: tested using German J.Engelsmann STAV II tap density tester.
[0096] The results are shown in Tables 2 and 3.
[0097] Table 2 Physical and chemical properties of porous carbon
[0098]
[0099] Table 3 Physical and chemical properties of silicon-carbon materials
[0100]
[0101] It can be seen from Tables 2 and 3 that when the specific surface area of the porous carbon is not much different and the silane deposition parameters remain unchanged, the silicon content in the silicon-carbon negative electrode can be basically kept consistent. This phenomenon is conducive to maintaining the uniform distribution of silicon nanoparticles in the porous carbon. The specific surface area of the porous carbon did not change dramatically with the increase of the template agent, but showed a trend of first increasing and then decreasing, but the change was not large. This may be because the increase in the initial template agent makes the activation of the carbon material easier, so the specific surface area of the porous carbon increases. However, when the pore volume of the mesopores reaches a certain level, the presence of too many mesopores causes the limited carbon source to be over-consumed, the proportion of micropores is reduced, and the specific surface area provided by the micropores is reduced.
[0102] As the template agent increases, the residual carbon rate shows a downward trend. This is mainly because the template agent is mainly composed of carbohydrates, in which the carbon content is low, resulting in a decrease in the residual carbon rate. The yield of porous carbon is related to the residual carbon amount and the mesopore ratio. A high residual carbon rate is beneficial to increase the yield of porous carbon, while a high mesopore ratio is beneficial to activation. However, a high residual carbon rate will reduce the mesopore ratio, so the yield of porous carbon first increases and then decreases.
[0103] The shape of the template agent makes the porous carbon retain part of the shape of the template agent, causing the mesopore shape to change from H1 and H2 to H3. With the increase of the template agent, the specific surface area of the mesopores increases, and the pore size of the mesopores is larger, resulting in an increase in the pore volume ratio, so that the tap density of the silicon-carbon negative electrode decreases with the increase of the template agent.
[0104] In addition, when the content of the template agent exceeds a certain range, the particle size change of the silicon-carbon negative electrode at different pressures becomes significant, and spontaneous combustion occurs at higher pressures, indicating that the strength of the silicon-carbon negative electrode material is greatly reduced. Although the presence of mesopores can reduce expansion and improve the initial efficiency, the significant reduction in strength is not conducive to the processing of the material. Therefore, the content and distribution of mesopores in the silicon-carbon negative electrode need to be strictly controlled to prevent them from sticking together to form macropores.
[0105] Effect Example 3 Electrochemical Performance
[0106] The following effect tests were performed on the intermediate products and the final silicon-carbon materials of the above embodiments and comparative examples:
[0107] (1) Button battery preparation
[0108] Preparation of negative electrode slurry and pole piece: The negative electrode formula is designed as CMC:PAA:SBR:SP:CNTs:silicon-carbon material:graphite=0.5:3.5:0.5:0.1:0.1:10:85.3 (by mass ratio). The negative electrode slurry preparation process is graphite→CMC→SP→CNTs→silicon-carbon material. After dispersing for 3 hours with a planetary disperser at a rotation speed of 300r / min and a revolution of 1000r / min, 80% deionized water is injected at one time and dispersed for 1 hour at a rotation speed of 500r / min and a revolution of 600r / min. PAA is added and dispersed for 1 hour at a rotation speed of 500r / min and a revolution of 500r / min. Finally, SBR is added and dispersed for 1 hour at a rotation speed of 300r / min and a revolution of 300r / min. The coated current collector is a copper foil with a thickness of 8 μm, coated on one side, with the coated side facing the negative electrode of the button battery. The thickness of the active material coated on one side is 40 μm, and the compaction density is 1.7 g / cm 3 , where the coating speed is 40 cm / s, the post-baking temperature is 80°C, and the drying time is 400s.
[0109] Electrolyte preparation: The electrolyte composition, by mass percentage, is: EC 10%, PC 15%, DEC 20%, PP 30%, LiPF6 15%, FEC 6%, PS2.5% and LiODFB 1.5%.
[0110] Half-cell preparation: The positive electrode uses the above single-piece negative electrode plate, the negative electrode uses a lithium sheet, and 0.5g of the above electrolyte is assembled into a CR2032 button battery, and the voltage serial port uses 0-1.5V. The entire battery is assembled in a glove box to avoid contact with air.
[0111] (2) Performance testing
[0112] ①0.1C 0.8V gram capacity: First, assemble a CR2032 button battery as above, then discharge it at a constant voltage of 0.1V / h to 0.000V, then charge it at 0.1V / h to 1.5V, and record the charging current of 0.1C; reassemble a CR2032 button battery, record the charging current of 0.1C, and perform a constant current charge and discharge test, discharge it to 0V and then charge it to 1.5V, with a cut-off current of 1mV. After obtaining the capacity, use the capacity / mass of active material in the electrode to obtain the gram capacity of 0.1C 0.8V.
[0113] ②First efficiency: First, assemble a CR2032 button battery as above, then discharge it at a constant voltage of 0.1V / h to 0.000V, then charge it at 0.1 / h to 1.5V, record the charge and discharge current, and get the first efficiency by discharging current / charging current.
[0114] ③ The expansion of the first lithium embedding cycle: (the thickness of the electrode after saturated lithium embedding - the thickness of the copper foil) / (the thickness of the electrode without lithium embedding - the thickness of the copper foil), and the compaction density is controlled at 1.7g / cm 3 .
[0115] ④ Number of cycles to failure: According to the above steps, for each silicon-carbon material, assemble a CR2032 button battery respectively, and then use constant voltage discharge method, discharge at 0.1V / h to 0.000V, charge at 0.1V / h to 1.5V, and record the charging current; reassemble a new CR2032 button battery, and perform constant current charge and discharge test with a charging current of 1C or 2C, repeatedly charge and discharge from 0V to 1.5V, record the discharge current, and terminate when the discharge current is 60% of the 0.1C 0.8V gram capacity, and record the number of cycles, which is the number of cycles to failure under the test conditions.
[0116] ⑤Rate retention rate: obtained based on the number of 2C cycle failures / 1C cycle failures.
[0117] The test results are shown in Table 4 below:
[0118] Table 4 Electrochemical properties of silicon-carbon materials
[0119]
[0120] As can be seen from the table above, the silicon content is basically the same, and the gram capacity is not much different. This is mainly due to the CO 2 The activation time is long enough, and for phenolic resin without template agent, the voids of carbon material can be fully developed; while for carbon material with template agent, the mesopores further promote the development of voids, making the overall performance similar. 2 The activation process makes the internal micropores well developed, which makes the silane deposition of the silicon-carbon anode more uniform and the CO 2 The activation process helps to eliminate the functional groups in the carbon material, so the gram capacity at 0.8 V is maintained at a high level.
[0121] Under given pressure conditions, material strength is the most critical factor affecting the first effect. It can be seen from the data that with the increase of template dosage, the change in particle size under different pressures shows that the use of less template agent will not affect the strength of porous carbon. This is mainly related to the carbonization of the template agent to form a buffer layer in the mesopores and the presence of the template agent causing the carbon layer around the mesopores to become disordered. On the contrary, the increase in the proportion of mesopores reduces the expansion of the silicon-carbon negative electrode, thereby improving the first effect, which is also the reason why Example 15 has better performance.
[0122] The amount of expansion in the first cycle of lithium insertion mainly depends on the proportion of mesopores. Under lower compaction, the amount of expansion is inversely proportional to the proportion of mesopores. In Examples 11-20, the overall parameters of the H3-type porous carbon formed based on cellulose nanocrystals are better than those of the porous carbon materials based on spherical starch templates. This is mainly because the toughness of the interstitial porous carbon is higher and it is not easy to break under high pressure density, while the ink bottle-type porous carbon has low toughness and high strength. Once a certain pressure is exceeded, the material will not be able to recover, and its performance is not as good as the silicon-carbon negative electrode material of the interstitial porous carbon. This can be seen from the change in particle size of the silicon-carbon negative electrode material under different pressures. The interstitial porous carbon performs better under high pressure. In addition, the superiority of porous carbon based on cellulose nanocrystals over spherical starch particles may be related to its internal filler. The crystallinity of high-strength cellulose nanocrystals is much higher than that of starch. This ordered structure makes the carbonization product of cellulose nanocrystals stronger than spherical starch particles, which helps to form a stronger buffering effect.
[0123] Furthermore, the first effect has a great influence on the rate performance of the battery. The first effect directly affects the interface impedance of the button battery, and the battery with lower interface impedance has better rate retention, as shown in the comparison between Example 5 and Example 1. In addition, the first effect also has a significant impact on the cycle parameters at low rates, because the interface impedance directly affects the internal resistance of the battery, which has a significant impact on the cycle and rate performance.
Claims
1. A porous carbon, characterized in that Its pore structure includes mesopores and micropores; In the pore structure, the pore volume of the mesopores accounts for 3-20%, and the pore volume of the micropores accounts for 80-97%; the adsorption-desorption isotherms of the mesopores are one or more of an H1 hysteresis loop, an H2 hysteresis loop, and an H3 hysteresis loop; The pore structure is filled with carbon particles, and the carbon particles are spherical carbon particles or spindle-shaped carbon particles.
2. The porous carbon according to claim 1, characterized in that The pore volume of the pore structure is 0.7-1.3 cm 3 / g; And / or, when the adsorption-desorption isotherm of the mesopore is an H1 type hysteresis loop and / or an H2 type hysteresis loop, the ID / IG of the porous carbon is 1.2-0.8, for example, 0.99, 0.98 or 0.97; when the adsorption-desorption isotherm of the mesopore is an H3 type hysteresis loop, the ID / IG of the porous carbon is 1.15-0.75, for example, 0.97, 0.96 or 0.95; the ID / IG value refers to the intensity ratio of the Raman D peak to the G peak; Preferably, the adsorption-desorption isotherm of the mesopores is an H3 type hysteresis loop; and / or, the spherical carbon particles are attached to the pore walls in a point contact manner; And / or, the diameter of the spherical carbon particles is 15-50 nm, for example 50 nm; and / or, the spindle-shaped carbon particles are attached to the pore walls in line contact or surface contact; And / or, in the spindle-shaped carbon particles, the particle size has a width of 4-28 nm and a length of 190-300 nm, for example, a width of 20 nm and a length of 300 nm.
3. A method for preparing porous carbon, characterized in that: The preparation method comprises the following steps: carbonizing and activating a mixture containing a carbon source and a template to obtain porous carbon; Wherein, the template agent is a spherical template agent or a shuttle-shaped template agent, the particle size of the spherical template agent is 5-200nm, the length of the shuttle-shaped template agent is 250-350nm, the width is 20-40nm, and the aspect ratio is 9-17.5; the material of the template agent is one or more of silicon dioxide, starch, cellulose nanocrystals and polymer materials with a molecular weight of 5000-50000; The mass ratio of the template to the carbon source is (5-50):
100.
4. The method for preparing porous carbon according to claim 3, characterized in that: The particle size of the spherical template agent is 20-80nm, for example 50nm; And / or, the spherical template agent is made of starch; And / or, the material of the shuttle-shaped template is cellulose nanocrystal; And / or, the carbon source is a resin carbon source and / or a biomass carbon source; Preferably, the resin carbon source is selected from one or more of phenolic resin, epoxy resin, furan resin, polyacrylic resin, polyurethane resin and polyacrylonitrile resin, such as phenolic resin; Preferably, when the carbon source is a resin carbon source, the mixture further comprises a curing agent; preferably, the curing agent is selected from one or more of urotropine, ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, hexamethylenetetramine, aniline, p-toluenesulfonic acid, formaldehyde, benzenesulfonyl chloride, p-toluenesulfonyl chloride, ethyl sulfate, petroleum sulfonic acid, dodecylbenzenesulfonic acid, polyoxymethylene, maleic anhydride, phthalic anhydride, isocyanate, pyridine, benzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide and cyclohexanone peroxide, such as urotropine; preferably, when the carbon source is a resin carbon source, the mass ratio of the resin carbon source to the curing agent is (10-20):1, such as 16.67:1; And / or, the mass ratio of the template to the carbon source is 5:1000, 10:1000, 15:1000, 20:1000, 25:1000, 30:1000, 35:1000, 40:1000, 45:1000 or 50:1000.
5. The method for preparing porous carbon according to claim 3, characterized in that: The carbonization step also includes a drying step; the drying step is preferably spray drying; Preferably, the spray drying temperature is 100-150°C, for example 130°C; and / or, before the carbonization, the particle diameter of the material is 5-20 μm, for example 8 μm; And / or, the carbonization adopts a staged heat treatment; preferably, the first stage has a heating rate of 1-10°C / min, the temperature is raised to 150-250°C, and the temperature is kept for 0.5-3h; the second stage has a heating rate of 1-10°C / min, the temperature is raised to 400-800°C, and the temperature is kept for 0.5-12h; And / or, the carbonization is carried out under an inert atmosphere, the gas flow rate of the inert atmosphere is 0.5-3 L·kg -1 min -1 , for example 1 L kg -1 min -1 ; and / or, after the carbonization, the particle size D50 of the material is 5-20 μm, for example 8.1 μm; And / or, the activation is carried out by CO2 activation or alkali activation; when CO2 activation is adopted, the gas flow rate is preferably 1-5 L·kg -1 min -1 , for example 2L·kg -1 min -1 ; The temperature is preferably 450-800°C, for example 550°C; The time is preferably 5-15h, for example 10h.
6. A porous carbon, characterized in that: It is prepared by the preparation method according to any one of claims 3 to 5.
7. A silicon-carbon material, characterized in that: It is a core-shell structure, the core of the core-shell structure comprises the porous carbon and silicon particles as described in any one of claims 1-2 and 6, and the shell of the core-shell structure is a carbon coating layer.
8. A method for preparing a silicon-carbon material, characterized in that: The porous carbon as claimed in claim 1 or 6 is sequentially subjected to silane deposition and carbon coating; Preferably, the gas for silane deposition is a mixed gas of silane and argon; preferably, the mixed gas is 20% silane and 80% argon, where % refers to volume percentage; Preferably, the ventilation volume of the silane deposition is 0.2-1 L·kg -1 min -1 , for example 0.5 L kg -1 ·min -1 ; Preferably, the temperature of the silane deposition is 500-600°C, for example 550°C; Preferably, the silane deposition time is 6-10 h, for example 8 h; Preferably, the carbon coating is carried out by acetylene coating; the ventilation volume of acetylene is preferably 1-3 L·kg -1 ·min -1 , for example 2 L·kg -1 ·min -1 The ventilation time of acetylene is preferably 500-700 min, such as 600 min; the temperature of the acetylene coating is preferably 500-700°C, such as 600°C.
9. A silicon-carbon material, characterized in that: It is prepared by the preparation method as claimed in claim 8.
10. Use of the porous carbon according to any one of claims 1 to 2 and 6 or the silicon-carbon material according to claim 7 or 9 in a battery.
Citation Information
Cited By
Porous carbon material for negative electrode with improved mechanical strength and preparation method of porous carbon material
CN120534970A
Porous carbon material for an anode with improved mechanical strength and method for producing the same
CN120534970B
Porous carbon particle and preparation method thereof, negative electrode active material and secondary battery
CN121282198A
Mesoporous carbon composite material and preparation method thereof
CN121516865A
Porous carbon material and preparation method thereof, and silicon-carbon composite material and preparation method thereof
CN121823577A